Rishtas: adding emotion to strategy in understanding British Pakistani transnational marriages - Shaw, A; Charsley, K (Blackwell Publishing, 2006)
The popularity of transnational marriages that in most cases involve first cousins or other kin distinguishes Pakistanis from other British South Asian groups. In this article we explain the popularity of such marriages. We seek to complement accounts that stress kinship obligations and socio-economic strategy by showing that transnational marriages are also motivated by the emotional ties of kinship. Central to this analysis is a focus on the Urdu/Panjabi concept of rishta, which conveys ideas about a 'good' match and about emotional connections between people. Our attention to emotional discourse between siblings, between parents and children and between prospective spouses in the context of marriage arrangements augments the understanding of what is at stake for those involved in transnational marriages. Our analysis also complements accounts that emphasize parental exegesis by offering a multigenerational perspective.